1999
DOI: 10.1046/j.1365-4362.1999.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and control of scabies in an Egyptian village

Abstract: Our data provide the first complete picture of the epidemiology of scabies in rural Egypt. The epidemiologic characteristics of the disease should be considered in the design of disease control programs for other villages with scabies epidemics. Our findings revealed that good control was achieved with the following: increased awareness and better case finding, education of the staff at the rural health unit, improved hygiene measures, and massive treatment campaigns using effective drugs such as topical perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
2
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 15 publications
5
36
2
2
Order By: Relevance
“…2) Topical Permethrin 5% cream single application: Earliar studies [4,[8][9][10] have reported cure rate >80% with Permethrin. Higher cure rates (98%) was reported after two applications.…”
Section: Discussionmentioning
confidence: 99%
“…2) Topical Permethrin 5% cream single application: Earliar studies [4,[8][9][10] have reported cure rate >80% with Permethrin. Higher cure rates (98%) was reported after two applications.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In resource-poor urban and rural communities the prevalence of the infestation with Sarcoptes scabiei may reach 10% in the general population and 59% in children. 1,2,4,7,9,[11][12][13][14][15][16][17][18][19] In an urban slum in Bangladesh, the incidence in children younger than 5 years was 952/1000/year, indicating that nearly all children experienced at least one infestation per year. 20 This is in contrast to the situation in industrialized countries, where the disease occurs sporadically in all age groups, particularly in sexually active adults, or causes epidemics in institutions and nursing homes.…”
mentioning
confidence: 99%
“…8,[21][22][23][24][25][26] Many factors have been suggested to determine the epidemiology of scabies in impoverished communities, including social attitudes, population movements, malnutrition, lack of access to health care, inadequate treatment, deficient hygiene, and crowding, but so far these assumptions have not been substantiated. 3,6,7 As in most countries scabies is not a notifiable disease, usually only large outbreaks tend to be reported. 27 By consequence, what is known about the epidemiology of scabies is mainly based on data from hospital and outpatient records or certain high-risk groups.…”
mentioning
confidence: 99%
“…They can be controlled through adequate water supplies that permit sufficient personal hygiene [6]. Examples of these include trachoma, a bacterial infection of the eyes, and scabies [13], a parasitic skin infection.…”
Section: Water-washed Diseasesmentioning
confidence: 99%